Translational approaches to restoring mitochondrial function in Parkinson's disease. Issue 5 (17th December 2017) - Mortiboys, Heather; Macdonald, Ruby; Payne, Thomas; Sassani, Matilde; Jenkins, Thomas; Bandmann, Oliver
Abstract : There is strong evidence of a key role for mitochondrial dysfunction in both sporadic and all forms of familial Parkinson's disease (PD). However, none of the clinical trials carried out with putative mitochondrial rescue agents have been successful. Firm establishment of a wet biomarker or a reliable readout from imaging studies detecting mitochondrial dysfunction and reflecting disease progression is also awaited. We will provide an overview of our current knowledge about mitochondrial dysfunction in PD and related drug screens. We will also summarise previously undertaken mitochondrial wet biomarker studies and relevant imaging studies with particular focus on 31P‐MRI spectroscopy. We will conclude with an overview of clinical trials which tested putative mitochondrial rescue agents in PD patients. Abstract :